2015
DOI: 10.1007/s00464-014-4045-1
|View full text |Cite
|
Sign up to set email alerts
|

Donor safety in live donor laparoscopic liver procurement: systematic review and meta-analysis

Abstract: Live donor laparoscopic liver procurement could be as safe as the conventional open approach. Lower blood loss and lower consumtion of analgesics might be offered in the laparoscopic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…The three studies[13,20,22] that evaluated recipient survival rate found no significant between-group difference. Other reports[38] evaluated several of the studies included in our meta-analysis, reporting survival rate but not postoperative liver function.…”
Section: Discussionmentioning
confidence: 99%
“…The three studies[13,20,22] that evaluated recipient survival rate found no significant between-group difference. Other reports[38] evaluated several of the studies included in our meta-analysis, reporting survival rate but not postoperative liver function.…”
Section: Discussionmentioning
confidence: 99%
“…EndoGIA staplers are widely used to manage vessels in laparoscopic nephrectomy because of their feasibility and safety and their use has become standard practice [19][20][21]. This is the reason why, we preferred EndoGIA from the beginning of our experience in patients underwent LDN [22].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical procedures in PLS should be carefully considered and well established [1,3,9,11,15,16], and we should consider that PLS commonly requires a longer operative time than OS [10]. Some researchers have reported advantageous points of PLS for LDs, such as less blood loss, less pain, a shorter hospital stay, and earlier social reintegration [3,5,6,14]. We also understand that many LDLT surgeons wish to attempt PLS for LDs [1,5,7,9,11,14].…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative damage should be minimized as much as possible, and an LD for LDLT is the best target for minimally invasive surgery [1,5,7,9,11-14] because he or she inherently requires no invasive surgical procedures. Additionally, a donor safety rate of 100% should be guaranteed [6,7,15,16]. …”
Section: Introductionmentioning
confidence: 99%